Sexual Harassment Cases in the Indonesian Broadcasting Commission Against Victims: How is the Law Enforcement? (Universitas Negeri Semarang, 2022)
In mid-2021, the Indonesian people were shocked by a news report about a case of same-sex sexual harassment carried out by employees of the central Indonesian broadcasting commission or better known as the central KPI. Which is, this case has been going on for a long time but due to the slow handling of the law, the victim also made an open statement to social media so that this case was widely discussed. The form of same-sex sexual harassment according to positive law is basically the same as sexual harassment against the opposite sex, only the difference lies in the perpetrator and the victim, namely the same sex. The elements of same-sex sexual harassment are the existence of an act related to sex, the form of the act is physical and non-physical and there is no voluntary action. The method of writing this article is based on normative law with a statutory approach and a case approach. The results of the research in this article show that there is evidence against perpetrators of same-sex sexual harassment by co-workers at the Central KPI. However, in accordance with the provisions of Article 184 paragraph (1) of the Criminal Procedure Code that evidence is carried out with the testimony of witnesses, expert statements, letters, instructions and statements of the defendant. Proving the crime of same-sex sexual harassment also requires the role of a doctor to provide medical information through visum et repertum so that cases of sexual harassment tend to get a slow legal process and result in changes in the mental pattern of the victim.